Principles of dry uniaxial compaction of ceramic nanopowder using ultrasonic action; Abstracts of the 5 International Conference on Nanostructured Materials ( August 20-25, 2000, Sendai, Japan) - Khasanov O. L. Oleg Leonidovich; Dvilis E. S.; Pokholkov Y. P. Yuri Petrovich; Sokolov V. M. (2000, 2000)
В фонде НТБ ТПУ отсутствует